Pendampingan Teknis dan Manajerial Tim Futsal Putri dalam Meningkatkan Kesiapan Menghadapi Kompetisi - Muhamad Muchsin; Muliyati Muliyati; Astari Rahim; Mustakim Mustakim; Didy Maharudin (GUYUB: Journal of Community Engagement, 2026)
This community service program aimed to improve the competition readiness of the FISIP Cenderawasih University Women’s Futsal Team through integrated technical, managerial, and psychological assistance. The initial assessment showed that the athletes’ average technical score was 66.1, management knowledge among team administrators was 49.6, and mental readiness was 64.2%. The program used a Participatory Action Research approach consisting of diagnosis, action planning and implementation, observation, and reflection involving 16 athletes, 2 coaches, and 5 administrators. The intervention was conducted from January to February 2026 through structured technical drills, tactical simulations, team management workshops, and mental strengthening sessions. The outcomes showed measurable improvement: the average technical score increased to 85.5 (up 29.4%), managerial knowledge rose to 85.2 (up 71.8%), and mental readiness reached 90.1% (up 40.3%). Tactical understanding also improved, indicated by 93.8% of athletes being able to apply team formations correctly and a 71% reduction in positional errors during match simulations. The team subsequently reached the final of the AAFI Series 1 Ramadhan Cup and won second place. The novelty of this program lies in the integration of technical, managerial, and mental assistance within one short-cycle mentoring model for women’s university futsal.